Emotional intelligence and women entrepreneurs / Shazwani Mohd Salleh ... [et al.] - Mohd Salleh, Shazwani; Nur Morat, Berlian; Baharuddin, Sitti Aminah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Emotional intelligence (EI) forms the stage at which cognition and emotion meet, it facilitates our capacity for resilience, motivation, empathy, cognitive, stress management, communication, and our ability to read. EI matters and if refined, affords one the opportunity to realise a more fulfilled and happy life. Moreover, EI has its roots in social intelligence; it is about having both interpersonal (ability to interact with others) and intrapersonal (cognitive skill to understand one's self) intelligence (Naseer, Chishti, Rahman, & Jumani, 2011). According to The Future of Jobs (2020), emotional intelligence is defined as being aware of others' reaction and understanding why they react as they do." Also, it is the ability to identify and manage own emotions.